Constrained fuzzy power flow - Eduardo Gouveia (2007)
In this paper a tool for the evaluation of transmission system adequacy is presented. Although similar in the basic assumptions to the classic versions of the Fuzzy Power Flow (FPF), the approach has significant differences in the formulation. First, it is symmetrical (no influence of the slack bus in the results), so all the fuzzy power injections are in the same situation. Second, by including line constraints, only feasible deterministic power flows are accepted in the fuzzy variables calculations, leading to a more correct representation of the possible impact of uncertainty. Third, recalculation of the estimated node fuzzy injections leads to a clear picture of the repressed power flows and thus of the adequacy of the grid. On the other hand, the Constrained Fuzzy Power Flow (CFPF) separates completely the analysis of the network from the generation influence and costs, which is indispensable in a unbundled organization of the power system.